Une nouvelle branche du droit international : Le droit international de la santé - Bélanger, Michel (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1982)
International health law is a soft law which is now reaching full maturity. It has gradually taken root since the middle of the 19th century, and it represents a synthesis of several disciplines (international work law, international social law, international humanitarian law, international medical law, international environment law, ...) International health law must be linked to international economic law and particularly to international development law. Moreover, it is mostly a Third-world law, especially since the World Health Organization (W.H.O.) caters first of all to the needs and demands of the developing nations. Thus it offers both an ideological and technical aspect which is very present in the concepts of New International Health Order and of Primarian Health Cares. W.H.O. must be considered as the main organization in the field of international public health, though, an international sanitary division has been established with both world organizations (mainly the United Nations System organizations), trans-regional, regional or sub-regional organizations, all with sanitary competence, as well as many non-governmental organizations with a sanitary purpose. The standardization process (general standards and ordinary standards) of international health law is nevertheless very advanced, and make international health law a half proclamatory and half executory law.